2007
DOI: 10.1080/03602550701558132
|View full text |Cite
|
Sign up to set email alerts
|

Characterization, Thermal, and Mechanical Behaviours of Gamma Irradiated Gum Arabic/Poly Vinyl Alcohol Polymer Blends

Abstract: Polymer blends based on various compositions of natural macromolecule gum arabic (GA) and poly vinyl alcohol (PVA) were prepared by solution casting technique. It was found that the maximum concentration of gum from which a compatible blend can be obtained was found to be from 10-30%. Compatible blend were exposed to gamma irradiation at different doses of 20, 30, and 50 kGy to evaluate the effect of irradiation on different properties of the blend. Physical, thermal and mechanical properties of the blend were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…This is due to the increase in the viscosity of reaction medium and thus restricting the movement of the free radical to reach the active sites on the polymeric substrate, so the lower degree of gelation was obtained [16]. This result is in coincidence with those reported by Mervat et al [17] who investigated the increase of the monomer concentration increased the percent of gelation in gum Arabic hydrogels. This result suggested that the presence of HEMA with GA enhanced the gelation process of the copolymers due to the difference in the diffusion coefficient of both polymers.…”
Section: A-effect Of Copolymer Compositionsupporting
confidence: 78%
“…This is due to the increase in the viscosity of reaction medium and thus restricting the movement of the free radical to reach the active sites on the polymeric substrate, so the lower degree of gelation was obtained [16]. This result is in coincidence with those reported by Mervat et al [17] who investigated the increase of the monomer concentration increased the percent of gelation in gum Arabic hydrogels. This result suggested that the presence of HEMA with GA enhanced the gelation process of the copolymers due to the difference in the diffusion coefficient of both polymers.…”
Section: A-effect Of Copolymer Compositionsupporting
confidence: 78%
“…Poly(vinyl alcohol) (PVA) is a polymer of great interest due to its desirable characteristics, specifically for various biomedical and pharmaceutical applications [1][2][3]. Polymer blending has been a most useful method for the improvement or modification of the physicochemical properties of polymer materials [4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%